Efficacy of GLP-1 analog to achieve metabolic control and correction of body weight in patients with type 2 diabetes mellitus - T. V. Saprina; T. K. Gudkova; V. A. Stolyarova; S. Yu. Martynova; N. G. Dudarkova; T. G. Yaroshevskaya; Yu. A. Kabirova; O. A. Pavlenko; I. N. Vorozhtsova (Бюллетень сибирской медицины)
Obesity associated with the enhanced risk of cardiovascular disorders plays a key role in the evolvement and progression of type 2 diabetes mellitus (DM2). Incretin mimetics are the sole class of hypoglycemic agents that not only effectively correct hyperglycemia but also reduce body weight. Exenatide (Byetta, Eli Lilly, USA) is the first drug of this class approved for the use as monotherapy. This paper presents data of clinical studies and owns data on the effectiveness of the drug Byetta in achieving metabolic control and weight correction in patients with type 2 diabetes.